Member commitment in agricultural cooperatives: Evidence from Ethiopia - Habtamu Mekonnen Awoke (Cogent Business & Management, 2021)
Member commitment is essential for the efficiency and survival of member-based economic organizations like agricultural cooperatives. In Ethiopia, cooperatives are considered as important vehicles for linking smallholder farmers to markets and for rural development more generally. However, member commitment in cooperatives is not self-evident. Different scholars confirm that there is a decline in commitment of members to their cooperative. Consequently, it is important to identify what factors drive this decline to enhance member commitment and promote the performance of cooperatives. Thus, this paper seeks to explore the determinants of member commitment. Our empirical analysis is based on a 2014 survey among 240 members of agricultural cooperatives in Ethiopia. This paper makes two contributions to the academic body of knowledge on member commitment in agricultural cooperatives. First, it distinguishes between three elements of commitment: loyalty, identification and participation. By exploring the determinants of each element of commitment, we obtain a much richer picture of what drives members. Second, we make a distinction between multipurpose cooperatives and specialized marketing cooperatives. The study has important implications for policy makers, government and stakeholders of cooperatives for devising appropriate interventions that could enhance the commitment of members in agricultural cooperatives.
Keywords: 650; agricultural cooperative; member commitment; loyalty; identity; participation; Ethiopia